PENGARUH TERAPI HIPNOTIS LIMA JARI TERHADAP KECEMASAN MASYARAKAT PADA MASA PANDEMI COVID-19 DI RW 007 KELURAHAN DELIMAKECAMATAN TAMPAN KOTA PEKANBARU - Anita Syarifah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Anxiety is an emotional state that arises when individuals are stressed and is characterized by feelings of tension, thoughts that make individuals feel worried and accompanied by physical responses. The number of confirmed cases of positive COVID-19 in Riau in 2021 was 31,541 cases. This causes increased anxiety in the community. One way to overcome anxiety is to use five finger hypnosis therapy. The purpose of this study to determine the effect of hypnosis therapy five fingers to the community during a pandemic anxiety Covid-19 in RW 007 Pomegranate Village District of the city of Pekanbaru 2021. Handsome Penel i tian using design quasy -eksperimen tal de ngan draft pre-post test with control group . Data collection was carried out using the Covid Peritraumatic Distress (CPDI) anxiety instrument . The sample was determined by purposive sampling method as many as 30 respondents with 15 intervention groups and 15 control groups. The s analysis was carried out by univariate analysis and bivariate analysis by using the Paired Sample T Test . Statistical test results obtained p value 0.000 <0.005, it can be concluded that there is an effect of five finger hypnosis therapy on public anxiety. It is expected that the public can apply hip therapy n otis five fingers to overcome anxiety .Keywords: Therapeutic Hypnosis Five Fingers, Anxiety, Covid-19.